The process of democratization during Najib Razak’s time - Mohd. Zain, Zawiyah; Yusoff, Mohammad Agus (AENSI Publisher, 2015)
Democratization aspect is important around the world, in the era of knowledge and information technology as the public is better educated and thus has high expectations to the government.In Malaysia, although a general election is held once in five years to elect a government, it is necessary to enhance the democratic aspect from time to time to achieve a better practice of democracy.This article is to discuss the issue of democratization in Malaysia, specifically during Najib Razak‟s time.The main objective of this article is to study the extent of democratization process which has already taken place and to analyze the factors leading to this process. The research methodology used is qualitative. Data obtained through in-depth interview of informants from government political parties, opposition parties, non-governmental organizations and academics. Face-to-face non-structured interview method is used whereby informants may respond without limitations, while focus is still on the research issue.The result shows that: first, the democratization process during Najib Razak‟s premiership is positive when the government started to open up the democratic space.Some of the outcomes are improvement in general election process, more freedom for public expression with the repeal of the Internal Security Act 1960 (ISA), introduction of the Peaceful Assembly Act 2012 and amendments to the Universities and University Colleges Act 1971.Second, the government has accommodated the democratization process due to demands from pro-democracy groups for improvements in terms of politics, general elections, justice and freedom of expression. In conclusion, democratic system in Malaysia has not reached a commendable level because of certain restrictions, to the extent that some scholars in their analysis describe Malaysia as a semi-democracy.Thus, several pro-democracy groups have emerged to demand ongoing democratization through their campaigns, demonstrations, protests or even political campaigns. During Najib Razak‟s time government has met the demands of certain pro-democracy groups and boosted the democratic process in Malaysia.